If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + 8) + 12 = 8(8x + 8) + 10 Reorder the terms: 9(8 + x) + 12 = 8(8x + 8) + 10 (8 * 9 + x * 9) + 12 = 8(8x + 8) + 10 (72 + 9x) + 12 = 8(8x + 8) + 10 Reorder the terms: 72 + 12 + 9x = 8(8x + 8) + 10 Combine like terms: 72 + 12 = 84 84 + 9x = 8(8x + 8) + 10 Reorder the terms: 84 + 9x = 8(8 + 8x) + 10 84 + 9x = (8 * 8 + 8x * 8) + 10 84 + 9x = (64 + 64x) + 10 Reorder the terms: 84 + 9x = 64 + 10 + 64x Combine like terms: 64 + 10 = 74 84 + 9x = 74 + 64x Solving 84 + 9x = 74 + 64x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-64x' to each side of the equation. 84 + 9x + -64x = 74 + 64x + -64x Combine like terms: 9x + -64x = -55x 84 + -55x = 74 + 64x + -64x Combine like terms: 64x + -64x = 0 84 + -55x = 74 + 0 84 + -55x = 74 Add '-84' to each side of the equation. 84 + -84 + -55x = 74 + -84 Combine like terms: 84 + -84 = 0 0 + -55x = 74 + -84 -55x = 74 + -84 Combine like terms: 74 + -84 = -10 -55x = -10 Divide each side by '-55'. x = 0.1818181818 Simplifying x = 0.1818181818
| 10(x+3)=10(x+3) | | 2x+2(x-4)=112 | | 3t+1+5t-7t=2+6 | | y=5x^2-2x-4 | | 2x^9-16x^7= | | 4(-4t^2+16t-7)=0 | | 0.7(6x+2)=1.1-(x+6)2x | | 8x-7y=5 | | x+6+x+3+3x-3+x^2-2x=46 | | 2v+40=8(5+v) | | 7.5x+2=6.5x | | p+p+30+p(4)-32=868 | | 12-20+125= | | 2(7x-5)= | | 18x-5=18x-6 | | 5(x+1)=-30+10+10x | | (12X-5X).4=252 | | 9x^2=36x-35 | | -2x-3+5x=-3 | | u^2-14u+49=2u^2-13u+29 | | -3y+8=-4y+6 | | -9y-1=-8y-5 | | 6y^3-4y^2-42y=0 | | 5(x+1)=10-10+10x | | -45+y= | | -5-6+20= | | -4a-28=-7(6a+4) | | 2d-d+5d= | | 5(x+1)=10+10+10x | | 777777+6664547-45463xp=555 | | 4x+4(x+20)=250 | | 15x^2-16x+15=0 |